USING OF ROD APPARATUS OF EXTERNAL FIXATION IN COMPLEX TREATMENT OF NO STABLE FRACTURES OF PELVIC BONES AT COMBINED INJURY - A. B. Tilyakov; E. Y. Valiev; B. S. Ubaydullaev (Неотложная медицинская помощь)
RELEVANCE. Our report is based on the results of investigation of 285 patients with different types of pelvic injury. due to clinic-anatomic variations of pelvic injuries and treatment tactics of victims were divided to three groups according to classification of the Center documentations AO. In the diagnosis of pelvic injuries method of multispiral computered tomography with modeling of volume images in 3d regime was used widely. In patients with combined injuries extra ostheosynthesis of pelvic bones was carried out after liquidation of dominant pathology. Ostheosynthesis of pelvic injuries was conducted using rod apparatus, offered by our clinic with stabilization and reposition of pelvic bone fragments. developed minimally invasive method with minimally traumatization of soft issues allows making ostheosynthesis in acute and early periods of traumatic disease at combined injury.